Studying the Effect of the Geometric Dimensions of the Bulbous Bow on the Resistance of the KCS Container Ship using CFD - حسام الدين محمد; بربهان ميشيل (Latakia University Journal -Engineering Sciences Series, 2024)
In this research, the flow field around the hull of the KCS container ship model was studied and analyzed through the use of CFD (Computational Fluid Dynamics) technology. Both the URANS (Unsteady Reynolds Averaged Navier Stokes) method and the k-ω SST turbulence model, available within the Ansys program, were used to solve the Navier-Stokes equations. The resistance of 9 different models of the KCS container ship with a bulbous bow was calculated with different values for both the length and width of the bulbous bow and fixing all the geometric dimensions of the ship. The quality of the numerical solution was initially confirmed by comparing the CFD results of the resistance with the experimental data. After that, the effect of changing the parameters of the bulbous bow on the total resistance and its components, and wave field was discussed and analyzed. Finally, study and analysis of the effect of the geometric parameters of the bulbous bow on the ship’s resistance was discussed and analyzed.